WITHDRAWN: A novel hybrid based on nature-inspired and Stochastic Fractal Search algorithms for optimizing of artificial neural network model in landslide susceptibility. (January 2023) - Moayedi, Hossein; Ahmadi Dehrashid, Atefeh; Gholizadeh, Mohammad Hossein
Abstract : This article has been withdrawn: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been withdrawn at the request of the Editor-in-Chief and publisher. The Editor-in-Chief regrets that an error in the review procedure occurred, whereby the article was accepted before assignment to a handling editor. The Editor-in-Chief and Publisher wish to apologise for any confusion or inconvenience caused; and we stress that the authors are not at fault in this case.